THE EFFECTIVENESS OF WORDUP APPLICATION TO ENRICH VOCABULARIES OF EFL LEARNERS’ : AN EXPERIMENTAL STUDY AT SMKN 1 CIREBON - Ibrahim Rizki, Muhamad; Sururi Asipi , Lili; Rosalina, Utami (Tomorrow's Education Journal, 2024)
This study aims to determine the effectiveness of using Wordup application as a medium for learning vocabulary on EFL learners at SMKN 1 Cirebon. The research methodology to be employed in this study is quantitative research. This research design incorporates a quasi-experimental design and a pretest-posttest control design, which were selected with the intention of drawing accurate conclusions regarding the impact of the independent variable on the dependent variableThe findings from the study clearly demonstrate the effectiveness of the wordup application. in the t test result showed that t count more than t table (3.110 1.660). Than, in the result paired sample t test showed that mean between pretest and posttest experiment and control have significant difference in the mean value (5.880 3.880). The students' vocabulary skills have difference significant between experiment and control class than wordup application have impact to enrich vocabulary skills at student tenth grade in SMKN 1 Cirebon.